A membrane-anchored aptamer sensor for probing IFNγ secretion by single cells. Issue 57 (4th July 2017) - Qiu, Liping; Wimmers, Florian; Weiden, Jorieke; Heus, Hans A.; Tel, Jurjen; Figdor, Carl G.
Abstract : Insight into the behavior of individual immune cells, in particular cytokine secretion, will contribute to a more fundamental understanding of the immune system. Abstract : Insight into the behavior of individual immune cells, in particular cytokine secretion, will contribute to a more fundamental understanding of the immune system. In this work, we have developed a cell membrane-anchored sensor for the detection of cytokines secreted by single cells using a combination of aptamer-based sensors and droplet microfluidics.